Impact of Digital Marketing on Consumer Behavior in Pokhara - Lamichhane, Baburam (KIC International Journal of Social Science and Management, 2022)
In this era of digitization, where everything is just a click away from us, marketing has evolved a lot. With the increased use of technology, smartphones, the producers of goods, can now reach consumers all over the globe. Thus, reaching out to consumers through the internet is digital marketing. Digital marketing, therefore, has an incredible influence on people’s interaction, work, purchases, and life habits. It is cost-effective too on the parts of the sellers and buyers. Thus, the present study examines the effectiveness and impact of digital marketing on the consumers’ behaviour in Pokhara city. The questionnaires were administered based on the purposive sampling method and obtained data from the respondents in Pokhara city. One hundred and seventy-two questionnaires were distributed, and 150 available samples were collected, except incomplete questionnaires, resulting in a response rate of 87.2 percent for all who chose to participate. Findings indicate that e-mail has a profoundly negative influence on consumer behaviour. Mobile, as a digital marketing channel, harms consumer behaviour. Social media marketing, SEO, and SEM affect consumer behaviour. Social media marketing is the most influential variable in consumer behaviour. We notice that the most significant effect on the consumer decision is in the evaluation state. This can be due to the social media marketing and the SEO and SEM channel directed to the consumer who has already been searching for the product.